2020
DOI: 10.1136/bmjdrc-2020-001519
|View full text |Cite
|
Sign up to set email alerts
|

Long-term lutein administration attenuates retinal inflammation and functional deficits in early diabetic retinopathy using the Ins2Akita/+mice

Abstract: IntroductionLutein is a carotenoid whose protective effects in the retina have been reported in various studies. The effect of lutein has not been reported in the retina of the Ins2Akita/+ mouse, a well-characterized genetic model for diabetic retinopathy (DR) in which the etiology of diabetes is better defined than the chemically induced diabetes. The objective of the present study is to investigate the effect of long-term administration of lutein in early stages of DR using the Ins2Akita/+ mouse.Research des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 50 publications
0
37
0
Order By: Relevance
“…• Anti-oxidative stress • Anti-inflammation • Anti-angiogenesis • Decrease of retinal neurons apoptosis [153][154][155][156][157][158] Carotenoids (Lutein, Zeaxanthin) [160][161][162][163][164] Anti-inflammation agents TNFα antagonist (Etanercept, Adalimumab, Infliximab)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…• Anti-oxidative stress • Anti-inflammation • Anti-angiogenesis • Decrease of retinal neurons apoptosis [153][154][155][156][157][158] Carotenoids (Lutein, Zeaxanthin) [160][161][162][163][164] Anti-inflammation agents TNFα antagonist (Etanercept, Adalimumab, Infliximab)…”
Section: Discussionmentioning
confidence: 99%
“…In type 2 diabetics, an increased thickness in the central fovea and improved retinal response density were observed after a two-year supplementation of combined lutein (10mg/day), zeaxanthin (2mg/day) and meso-zeaxanthin (10mg/day) [ 162 ]. The studies using diabetic animal models to investigate lutein and zeaxanthin effects have also demonstrated protection from diabetes-induced retinal apoptosis, abnormal capillaries formation, and visual dysfunction through decreased ROS, and inflammatory factors such as VEGF, IL-1β, and NF-ΚB in the retina [ 159 , 163 , 164 ].…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Lutein, a natural dihydroxycarotenoid, can be obtained from a wide variety of fruits and vegetables [ 16 ]. Dramatically, lutein has been reported to inhibit inflammation in diabetic retinopathy (DR) [ 17 ] and coronary artery disease [ 18 ] and exert antioxidative effects on cerebrovascular endothelial cells [ 19 ] and retinal pigment epithelial (ARPE-19) cells [ 20 ]. Moreover, many randomized clinical trials have reported that a lutein-rich diet decreases the incidence of nonalcoholic fatty liver disease [ 21 ], age-related macular degeneration (AMD) [ 22 ], breast cancer [ 23 ] and cognitive dysfunction [ 24 ] and reduces the risk of cardiovascular events, including atrial fibrillation [ 25 ], atherosclerosis [ 26 ] and hypertension [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Along with zeaxanthin, it is the only carotenoid that is found in the macula of the eye after crossing the blood-retina barrier [155]. Treatment with lutein attenuates retinopathy associated with photo stress, inflammation, and oxidative stress [156][157][158], and dietary lutein prevents aging-and diabetes-related eye diseases [159,160]. Lutein also crosses the blood-brain barrier to allow for delivery to various regions of the brain.…”
Section: Luteinmentioning
confidence: 99%